2018
DOI: 10.1590/18069657rbcs20170270
|View full text |Cite
|
Sign up to set email alerts
|

Visual Evaluation of the Soil Structure under Different Management Systems in Lowlands in Southern Brazil

Abstract: The "Visual Evaluation of Soil Structure" (VESS) is a method used primarily to evaluate the soil structural quality of Oxisols in Brazil and secondly for more specific research, consultancy, and teaching purposes. Since the methodology was never applied and compared with laboratory evaluations of physical properties of hydromorphic soils of the Pampa biome in the south of Brazil, this study evaluated the use of VESS as a visual indicator of the structure quality of a typic eutrophic Albaqualf soil under native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
7
17
1
Order By: Relevance
“…The lower VESS scores under CT treatments compared to RT and NT systems indicated a reasonably good soil structural quality despite the increase in tillage density (Figure ). In contrast to our findings on good soil structural quality under CT systems, Tuchtenhagen, Lima, Bamberg, Guimarães, and Mansonia () reported better soil structural quality with the absence of tillage under native grass compared to CT system. Better soil quality under native grassland was attributed to the lack of tillage, high plant residue and higher organic matter content in surface layers.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The lower VESS scores under CT treatments compared to RT and NT systems indicated a reasonably good soil structural quality despite the increase in tillage density (Figure ). In contrast to our findings on good soil structural quality under CT systems, Tuchtenhagen, Lima, Bamberg, Guimarães, and Mansonia () reported better soil structural quality with the absence of tillage under native grass compared to CT system. Better soil quality under native grassland was attributed to the lack of tillage, high plant residue and higher organic matter content in surface layers.…”
Section: Resultscontrasting
confidence: 99%
“…Significant positive correlations ( p < 0.01) of PR measurements with VESS scores at three depths show the effectiveness of VESS method in detecting compacted layers (Table 6). Similar to our results, significant relationships have been reported between VESS scores and physical soil quality attributes for different types of soils (Castioni et al., ; Cherubin et al., ; Tuchtenhagen et al., ). The PCA analysis using the varimax rotation and components extraction with Eigenvalues ≥1.0 yielded four principal components (PCs) that collectively accounted for the 80.64% variance in data (Table ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Also, it has been a great alternative for researchers and farmers, as it enables the analysis of soil layers via the verification of soil attributes such as aggregate stability, size, and porosity, besides root system behavior, among other characteristics. Many studies have used such method to distinguish management systems of both long term [14][15][16] and short term [17]. Munkholm and coauthors [18] found lower visual scores for a crop rotation system with barley and oat than for maize monoculture and maize-soybean succession, showing the effect of forage grasses on soil structural quality.…”
Section: Introductionmentioning
confidence: 99%